2018
DOI: 10.1039/c8cc08440h
|View full text |Cite
|
Sign up to set email alerts
|

Site-selective metallation of dicarbene precursors

Abstract: Heterobimetallic bis-NHC complexes have been obtained by the site-selective metallation of imidazolium/2-chlorobenzimidazole bis-NHC precursors using two different reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 43 publications
0
22
0
1
Order By: Relevance
“…We have noted previously that Pd II C-azolato complexes obtained by oxidative addition of 2-halogenoimidazole or 2-halogenobenzimidazole derivatives tend to form dinuclear species by nucleophilic attack of the unsubstituted azolato ring nitrogen atom at the metal center of a second complex molecule with elimination of one ligand. ,, The formation of such dinuclear species is less common for the more substitution inert Pt II complexes, where the mononuclear azolato complex has been isolated . No dinuclear complexes have been detected in the oxidative addition of 8-halogenotheophyllines to [Pd­(PPh 3 ) 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have noted previously that Pd II C-azolato complexes obtained by oxidative addition of 2-halogenoimidazole or 2-halogenobenzimidazole derivatives tend to form dinuclear species by nucleophilic attack of the unsubstituted azolato ring nitrogen atom at the metal center of a second complex molecule with elimination of one ligand. ,, The formation of such dinuclear species is less common for the more substitution inert Pt II complexes, where the mononuclear azolato complex has been isolated . No dinuclear complexes have been detected in the oxidative addition of 8-halogenotheophyllines to [Pd­(PPh 3 ) 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the activation barriers to reach these products differ for the reactions with Ni 0 and Pd 0 . In contrast to benzimidazolato and imidazolato palladium­(II) complexes, ,, the theophyllinato complexes [ 1 ]–[ 3 ] show no tendency to form dinuclear derivatives by attack of the unsubstituted ring nitrogen atom N9 at another complex molecule. This is apparently a consequence of the electron-poor theophylline backbone, which reduces the nucleophilicity of atom N9.…”
Section: Discussionmentioning
confidence: 99%
“…The proton source py ⋅ HBF 4 was added to convert the azolato complex initially formed in the oxidative addition into the p NHC complex. Without the N‐protonation, the azolato complexes often exhibit a tendency to form dinuclear complexes through an attack of the strongly basic unsubstituted ring‐nitrogen atom N24 at a metal center of a second complex molecule [8a,9a,d,11a] …”
Section: Methodsmentioning
confidence: 99%
“…However, certain examples have shown that the heterometallic NHC-M C complexes formed during the treatment of the corresponding metalcontaining imidazolium salts with Ag 2 O [152][153][154][155][156][157] or Cu 2 O [115] are stable and can be isolated. The similar heterometallic NHC-M C complexes (pre-synthesized or generated in situ) can be involved in the transmetalation reaction at the M C atom with preservation of the other metal coordinated at the neighbor covalently bound ligand (Scheme 30) [114,115,[158][159][160][161][162][163][164][165][166][167][168][169][170][171][172]. A common feature of these examples is that the potential carbene-accepting metal in the structure of such complexes is strongly chelated [114, 115, 158-163, 167, 168] or involved in a metallocene [164-166, 171, 172] and, hence, cannot be involved in the transmetalation.…”
Section: Transmetalation Retaining the Other Atom In The Productmentioning
confidence: 99%